Spatial distribution and population dynamics of free-roaming (stray and semi-domiciled) dogs in a major Brazilian city - de Santi, Carlos Eduardo; Chiba de Castro, Wagner Antonio; Sibim, Alessandra Cristiane; Lopes, Renata Defante; Galvão, Sandro Roberto; Kurtz, Giselli Maria; Biondo, Leandro Meneguelli; Kmetiuk, Louise Bach; Biondo, Alexander Welker (Frontiers in Veterinary Science, 2024)
Although estimate models have been proposed to determine free-roaming (stray and semi-domiciled) dog populations, to date no study has focused on the three major border areas of Brazil. Therefore, the present study assessed the free-roaming dog population of Foz do Iguaçu, a major far-west Brazilian city located in a three-border area (Brazil, Argentina, and Paraguay), which is considered among the top 5 Brazilian tourist destinations. Three capture-release samples populations with a 6-month interval and 10-day duration were performed, totaling 18 months, between 2018 and 2019. A total of 1,273 dogs were estimated at the first (95% Confidence Interval 468-2,078 dogs), 904 at the second (95% CI 452-1,355 dogs) and 1,564 at the third (95% CI 521-2,607 dogs) capture in this area, suggesting a population density of 18.4 dogs/km 2 (6.1-30.6 dogs/km 2 , 95% CI). Of all free-roaming dogs, 452/1,125 (40.2%) were stray with no confirmed ownership or household, 672/1,125 (59.8%) had a known origin, of which 625/1,125 (55.6%) were semi-domiciled with ownership or a household, 36/1,125 (3.2%) were neighborhood dogs with maintainers, and 11/1,125 (1.0%) were owned by recycling material collectors and homeless individuals. Most of the 1,125 dogs (862/1,125; 76.6%) had an ideal body condition score. The high outdoor access of owned dogs herein may be a result of cultural behavior. However, because 533/1,125 (47.4%) of the free-roaming dogs presented with clinical abnormalities, irresponsible ownership may have negatively impacted dog health and welfare. This study was the first to establish the density of free-roaming dogs, ratio of stray and semi-domiciled dogs, and their dynamics over time in Foz do Iguaçu. The findings may serve as a warning for the high level of dog outdoor access and irresponsible guardianship, which may negatively affect animal health and welfare, leading to diseases, accidents, trauma, and animal cruelty.